Identification af explosive power factors as predictors of player quality in young female volleyball players - Grgantov, Z.; Milic, M.; Katic, R. (Collegium Antropologicum, 2013)
With the purpose of determining the factor structure of explosive power, as well as the influence of each factor on situational efficiency, 56 young female volleyball players were tested using 14 tests for assessing nonspecific and specific explosive power. By factor analysis, 4 significant factors were isolated which explained the total of over 80% of the common variability in young female volleyball players. The first factor was defined as volleyball-specific jumping, the second factor as nonspecific jumping and sprinting, the third factor as throwing explosive power, while the fourth factor was interpreted as volleyball-specific throwing and spiking speed from the ground. Results obtained by regression analysis in the latent space of explosive power indicate that the identified factors are good predictors of player quality in young female volleyball players. The fourth factor defined as throwing and spiking speed from the ground had the largest influence on player quality, followed by volleyball-specific jumping and nonspecific jumping and sprinting, and to a much lesser extent, by throwing explosive power. The results obtained in this age group bring to the fore the ability of spiking and serving a ball of high speed, which hinders the opponents from playing those balls in serve reception and field defence. This ability, combined with a high standing vertical jump reach and spike approach vertical jump reach (which is the basis of the 1st varimax factor) enables successful performance of all volleyball elements by which points are won in complex 1 (spike) and complex 2 (serve and block). Even though the 2nd factor (nonspecific jumping and sprinting) has a slightly smaller impact on situational efficiency in young players, this ability provides preconditions i.e. preparation for successful realisation of all volleyball elements, so greater attention must be paid to perfecting it in young female volleyball players.